Physico-chemical properties and consumer acceptance of instant cowpea(Vigna unguiculata) powder for complementary food (2012)
"Two cultivars of cowpea (white and brown testa coloured) were processed by pre-cooking for 10min and dry-toasting (170°C, 10min) to render them ready-to-eat and to inactivate the anti-nutritional factors. The samples were dry-milled into powders. Ogi, traditional gruel from maize, was produced into powder. Five different blends of ogi and cowpea powder were prepared. Proximate chemical composition including Trypsin inhibition activity of the various blends was investigated. Also functional characteristics of the samples including bulk density, gelation capacity and water absorption capacity and water absorption capacity were investigated. Ogi supplemented with cowpea powder and 100% ogi were prepared into porridges which were presented for sensory evaluation among members of the university community. Each sample was evaluated for colour, taste, mouth-feel, flavour and overall acceptance. Moisture content values of the processed cowpeas ranged from 6.05 to 7.22% for boiled white cowpea and boiled brown cowpea respectively. Protein content ranged between 22.8% in the boiled white cowpea and 25.4% in the raw brown cowpea. There were 88.6-93.3% and 77.7-88.6% reduction in Trypsin inhibitor activity (TIA) of both white and brown cultivars of cowpea respectively. Sensory evaluation of ogi supplemented with cowpea revealed that supplementation at level above 30% is not acceptable among the panel. Brown cultivar of cowpea was preferred to the white cultivar. "